PERBAIKAN TATA LETAK LANTAI PRODUKSI INDUSTRI MEBEL MENGGUNAKAN METODE GRAFIK DAN ALGORITMA CRAFT - Kuswanto Kuswanto; Juan Junius; Anita Christine Sembiring (Universitas Putera Batam, 2020)
Facility layout is integrated planning of the flow of a product in an operating system to obtain the most effective and efficient interrelation between workers, materials, machinery, and equipment as well as handling and transferring materials. A company engaged in furniture manufacturing has a problem in its production process, namely, the distance between machines is too far so that it affects the cost of handling materials. Distant workstations are found on profile machines, milling machines, measuring machines, cutting machines. Therefore, improvements must be made to the layout of facilities on the production floor so that facility layout is efficient and material handling costs are reduced. The problem-solving approach used is the Graph Method and CRAFT Algorithm. The results of the research show that material handling costs are reduced by 7.58% or Rp. 17,765 using the CRAFT algorithm.